Decolonizing Pathways towards Integrative Healing in Social Work - Clarke, Kris (Taylor & Francis, 2021)
Taking a new and innovative angle on social work, this book seeks to remedy the lack of holistic perspectives currently used in Western social work practice by exploring Indigenous and other culturally diverse understandings and experiences of healing. This book examines six core areas of healing through a holistic lens that is grounded in a decolonizing perspective. Situating integrative healing within social work education and theory, the book takes an interdisciplinary approach, drawing from social memory and historical trauma, contemplative traditions, storytelling, healing literatures, integrative health, and the traditional environmental knowledge of Indigenous Peoples. In exploring issues of water, creative expression, movement, contemplation, animals, and the natural world in relation to social work practice, the book will appeal to all scholars, practitioners, and community members interested in decolonization and Indigenous studies.